A FILOSOFIA DA PRÁXIS NA FORMAÇÃO POLÍTICA NO ENSINO MÉDIO - RAQUEL DAIANA ZIELINSKI TREVISAN (2024)
ZIELISNKI, Raquel Daiana. The philosophy of praxis in political education in high school. 2024. 130 f. Dissertation. (Master's Degree in Philosophy – PROF-FILO) from the Federal University of Mato Grosso do Sul, Campo Grande, MS, 2024. The present dissertation aims at the production of classes, which can be used for the continuation of the subject of political philosophy, treated in the 2nd year of high school, suggesting didactic sequencing and approach strategies that offer alternatives to teachers that intend to elucidate from common sense the philosophical critical thinking, from the political concepts of hegemony, Philosophy of praxis and democracy. It presents as a presupposition that the problematic of political philosophy has its subject dealt with only up to the conception of Marxist theory. The practical intervention takes place at the Vespasiano Martins State School, located in Campo Grande - MS, with students in the 2nd year of full-time high school, during the 2023 school year, and consists of the presentation of the thought of the philosopher Antonio Gramsci, his life trajectory, and the explanation of key concepts for the emancipation of the student, in relation to their political participation in society. With texts for interpretation and debates in class, together with the presentation of the film "A ONDA" as a form of suggestion to discuss the concepts to be studied, with writing activity and the application of a questionnaire. The form of research chosen is action research with the qualitative measurement of learning, obtained through the form of written evaluation. Keywords: Gramsci; Hegemony; Philosophy of praxis; Democracy.